PENINGKATAN KUALITAS SDM PAPUA MELALUI PELATIHAN PENGGUNAAN APLIKASI GOOGLE CLASSROOM UNTUK MENUNJANG PEMBELAJARAN DARING DI JAYAPURA - Feby Seru; Bobi Frans Kuddi (LPPM Uncen, 2022)
The COVID-19 pandemic has had an impact on education in Indonesia. The learning process that was initially carried out at school became learning carried out from home online. This condition caused the unpreparedness of various parties, including students who live at the Balim Yalimo Orphanage in Jayapura City. To overcome this, PKM activities are carried out which aim to improve the ability of students at the orphanage, in using the Google Classroom application as a support for online learning. The method used is a training and mentoring which consists of 3 stages, namely the preparation, implementation, and evaluation stages. The results obtained are that from 70% of participants who use Google Classroom as an online learning application, there are 43% of participants who are able to use the application well. However, after participating in the training, there was an increase in the ability of participants to use the Google Classroom application by 42%.Keywords: application; google classroom; training; online learning